Automated Collection Planning for Civilian and Commercial Satellite Imagery, and Definition and Exploitation of the Collection Asset Specification Data Structure - Jeff Secker; Katerina Biron; Dany Dessureault; Pierre Lamontagne; Rodney Rear (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
There are more than 8000 traditional and small/microsatellites in low Earth orbit (LEO) and many of these are civilian and commercial satellites for remote sensing and space-based intelligence, surveillance and reconnaissance (ISR). Collection planning is the first step in the tasking, collection, processing, exploitation, and dissemination (TCPED) process and is required to choose the collection assets (satellites), instrument modes, and orbital passes that best match the collection task. Collection planning requires understanding and experience with: requirements; satellite and instrument phenomenologies, and capabilities; collection strategies; and data processing and exploitation methodologies. Given this, it is challenging for collection managers to make the best use of available satellites in the time available, and they would benefit from automation in the collection planning processes and systems. This article defines and describes collection planning terminology, notation, and processes. It defines new metrics for assessing the temporal coverage (completeness and density of collection opportunities along the time axis), and it describes six semiautomated tools and their underlying algorithms. These can be used by a collection manager to automate elements of the collection planning process, and they can be used for machine-to-machine communication using web services, thereby decreasing the total time required. This machine-to-machine communication permits the collection planning process to be completed in seconds instead of minutes or hours, time which can be critical for dynamic tasking such as tip and cue or last-minute retasking situations.